Increasing the Thermal Efficiency of Double Tube Heat Exchangers by Using Nano Hybrid - Mohamad Hosein Barzegar; Mohamad Fallahiyekta (Ital Publication, 2018)
In this study overall heat transfer in a double pipe heat exchanger fitted with twisted-tape elements and hybrid nanofluid were studied experimentally. Hybrid nanoparticles with a diameter of 20nm and a concentration of 1% (w/w) were prepared. The effects of temperature, mass flow rate, concentration of nanoparticles on the overall heat transfer coefficient and heat transfer changes in the turbulent flow regime were investigated. The results showed that when both of twisted tape and nanofluid have been used, heat transfer coefficient was about 40 percent higher than when they were not used. The experimental results also showed that 1% Al2O3/CuO nanofluid with twisted tape has slightly higher heat transfer when compared to 1% hybrid nanofluid without twisted tape. Neural networks used for modeling the system. The dependency of overall heat transfer coefficient of nanofluid (OHTCNF) on Reynolds number have depicted. The correlation coefficient for all data 0.98 is the successful prediction is shown. In this experimental work, nanoparticles were dispersed in hot current and cold water absorbed heat from hot nanofluid, so this system could be a good candidate for using in food industries, because at the end of this process there isn't any needs of extracting nanoparticles from the cold current. The heat transfer rate from the heating fluid was calculated by some known equations.